Economic Development of Ski Industry in Experimental Innovation: Example of Palandoken Turkey and Alps Switzerland - TURGUTER, YAVUZ (ELSEVIER SCIENCE BV, 2015)
Sport contributions to people health, social development also it regulates social with unity and solidarity. All people around the World accepts existence of sport benefits. In this age, sport base on economy that is extends domestic and international tourism and one of the winter sport. In the World, most preferred winter sport is Ski. Palandoken is most suitable sport facility respecting to season conditions and facility sufficiency in our country. Alps is one of example in the World at Switzerland. Switzerland, hosts 30.000.000 Ski Lover which is that amount equal to 4 times Switzerland's population at Alps. That amount of tourist came to Turkey in 2012. (C) 2015 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: economic development; ski industry; innovation; palandoken